The Liquidity Channel of Fiscal Policy - Christian Bayer; Benjamin Born; Ralph Luetticke (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We provide evidence that expansionary fiscal policy lowers the return difference between more and less liquid assets—the liquidity premium. We rationalize this finding in an estimated heterogeneous-agent New-Keynesian (HANK) model with incomplete markets and portfolio choice, in which public debt affects private liquidity. In this environment, the short-run fiscal multiplier is amplified by the countercyclical liquidity premium. This liquidity channel stabilizes investment and crowds in consumption. We then quantify the long-run effects of higher public debt, and find a sizable decline of the liquidity premium, increasing the fiscal burden of debt, but little crowding out of capital.
Keywords: C11; D31; E32; E63; 330; fiscal policy; liquidity premium; business cycles; Bayesian estimation; incomplete markets; HANK